Penerapan Zahir Accounting Versi 5.1 Pada Pengolahan Data Akuntansi Butik - Dede Euis Sri Mulyatin; Fajar Agustini (LPPM Universitas Bina Sarana Informatika, 2022)
The development of information technology requires all fields of activity to be computerized. Manual accounting still has many weaknesses, so an accounting application that can support the bookkeeping of financial statements is needed. Boutiques require accounting data processing to support business activities in making financial reports. For this reason, the author makes research on processing accounting data at boutiques using Zahir Accounting Version 5.1, because until now the boutiques are still using manual recording. Boutique is a company engaged in the clothing trade. The system used at this time is still manual, starting from transactions and making financial reports. This is what causes errors in recording, inaccurate data so that reports are late in being presented to company management. Accounting data processing using Zahir Accounting Version 5.1 is the right solution in solving problems that exist in the Boutique. This application is effective and efficient in overcoming problems related to manual accounting records that are currently being run. Keywords: Financial Statements, Application of Accounting Applications, Zahir Accounting 5.1